A COMPARATIVE STUDY BETWEEN QUANTUM MECHANICS AND YOGĀCĀRA BUDDHISM ON PROPERTIES OF MATERIAL OBJECTS - Chen, Ven. Hui (The Journal of International Buddhist Studies College, 2019)
With the development of quantum mechanics, the knowledge of properties of material objects has greatly changed from the common ideas found in classic physics. Since Yogācāra is considered to be one of most compatible Buddhist theories with modern science this article aims at comparing quantum mechanics and Yogācāra on properties of material objects from three aspects: the source of material objects; their substantiality; and the interference from the mind. By doing this, a conclusion is made that the two have the same opinions at a general level but different opinions, to certain extents, from each other at speciﬁ c levels.